PARTISIPASI MASYARAKAT LOKAL DALAM PENGEMBANGAN DESA WISATA SIDETAPA KECAMATAN BANJAR KABUPATEN BULELENG - Kadek Noviani; I Gusti Ngurah Aan Darmawan (Cultoure: Jurnal Ilmiah Pariwisata Budaya Hindu, 2023)
Community participation is the main element that needs to be considered in the process of developing a tourism village. Bali has 238 tourist villages, one of which is the Sidetapa Tourism Village which is based on nature and culture. Sidetapa Tourism Village has been inaugurated as a tourist village since 2017, but until now the development of Sidetapa Village has not been seen. This study aimed at: (1). finding out the forms of community participation in the development of Sidetapa Tourism Village, Banjar District, Buleleng Regency, (2). determining the level of community participation in developing Sidetapa Tourism Village, Banjar District, Buleleng Regency, (3). finding out the supporting and inhibiting factors of the community to participate in the development of Sidetapa Tourism Village, Banjar District, Buleleng Regency. This study used a qualitative method with a type of phenomenology. This study used data collection techniques in the form of observation, interviews and documentation. The data analysis technique used is data reduction, data presentation and conclusion. The results of the study show that the community has indeed participated but not as a whole. The forms of participation provided by the community are in the form of ideas or ideas, energy, property, proficiency and skills as well as social. The level of community participation is at the consultation stage, where there is reciprocal communication, the community is free to participate in government programs but there is still control from the government. The findings in the field also reveal the supporting and inhibiting factors that influence community participation. It is expected that the community in general will be routinely given socialization and training related to tourism villages so that people will better understand the role of the community as the main actors in tourist villages. The implication of this research is that community participation in Sidetapa Village is quite good, but it will be even better, if in the future all parties related to tourism need to provide special outreach to local communities. So that people understand more about what to do.